A new species of the genus Basidissus (Coleoptera: Anthribidae) from east Madagascar, with a key to species - Trýzna, Miloš; Baňař, Petr (Zootaxa, 2013)
A new species, Basidissus bendai Trýzna & Baňař sp. nov. (Anthribidae: Anthribinae: Platyrhinini), from east Madagascar is described, female genitalia are studied and illustrated, and the mobility of the stylus of the toothed plate is discussed. Colour photographs as well as a key to Madagascan species of the genus Basidissus are provided.